Sebuah Studi PENGARUH SERVICE QUALITY, DIGITAL MARKETING DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN MENJADI NASABAH BANK SYARIAH DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (Studi Pengguna BSI pada Masyarakat Di Kab. Pati): Bahasa Indonesia - Ahmad Rif'an; Ari Setiawan (Jurnal Keuangan dan Perbankan Syariah, 2025)
Abstract This study aims to determine the effect of service quality, digital marketing and electronic word of mouth on the decision to become a customer of a sharia bank with brand image as an intervening variable. The population of this study was the people of Pati Regency who have Bank Syariah Indonesia. The sample in this study was 100 respondents using random sampling techniques. The author used a quantitative method where the data source was obtained from primary data. This research tool uses SPSS version 30. Data analysis uses instrument tests, statistics, classical assumptions and path analysis. The results of this study prove that: service quality, digital marketing and electronic word of mouth have a positive and significant effect on the decision to become a BSI customer. Brand image has a positive but insignificant effect on the decision, service quality does not affect brand image, digital marketing and electronic word of mouth have a positive and significant effect on brand image. However, brand image is unable to mediate service quality on the decision to become a BSI customer. Brand image is unable to mediate digital marketing on the decision to become a BSI customer. Brand image is unable to mediate electronic word of mouth on the decision to become a BSI customer.